53.3k views
5 votes

\rm\int_(0)^(2021) \frac{ \sqrt{x + \sqrt{x + \sqrt{x + √(x) + \cdots } } } }{1 + \sqrt{x - \sqrt{x - \sqrt{x - √(x - \cdots) } } } } dx \\

1 Answer

1 vote

We have the identity


(a + b)^2 = a^2 + 2ab + b^2 = a^2 + ab + b (a + b) \\\\ ~~~~ \implies a + b = √(a^2 + ab + b (a + b)) \\\\ ~~~~ \implies a + b = \sqrt{a^2 + ab + b \sqrt{a^2 + ab + b \sqrt{a^2 + ab + b √(\cdots)}}}

assuming
a+b\ge0.

For the numerator, let
b=1, so
a\ge-1, which means


a^2 + a = x \implies a = \frac{-1 + √(1 + 4x)}2

and so


\sqrt{x + \sqrt{x + \sqrt{x + √(\cdots)}}} = \frac{-1 + √(1 + 4x)}2 + 1 = \frac{1 + √(1 + 4x)}2

For the denominator, let
b=-1 so that
a\ge1. Now


a^2 - a = x \implies a = \frac{1 + √(1 + 4x)}2

so that


\sqrt{x - \sqrt{x - \sqrt{x - √(\cdots)}}} = \frac{1 + √(1 + 4x)}2 - 1 = \frac{-1 + √(1 + 4x)}2

So, in the integral we can simplify and evaluate it to


\displaystyle \int_0^(2021) \frac{\sqrt{x + \sqrt{x + \sqrt{x + √(\cdots)}}}}{1 + \sqrt{x - \sqrt{x - \sqrt{x - √(\cdots)}}}} \, dx \\\\ ~~~~~~~~ = \int_0^(2021) \frac{\frac{1 + √(1 + 4x)}2}{1 - \frac{1 - √(1+4x)}2} \, dx \\\\ ~~~~~~~~ = \int_0^(2021) (1 + √(1 + 4x))/(1 + √(1 + 4x)) \, dx \\\\ ~~~~~~~~ = \int_0^(2021) dx = \boxed{2021}

User Alexander Block
by
4.7k points